2000
DOI: 10.1038/sj.ijo.0801198
|View full text |Cite
|
Sign up to set email alerts
|

The effects of 18 months of intermittent vs continuous exercise on aerobic capacity, body weight and composition, and metabolic fitness in previously sedentary, moderately obese females

Abstract: OBJECTIVES:To compare the effects of 18 months of continuous vs intermittent exercise on aerobic capacity, body weight and composition, and metabolic ®tness in previously sedentary, moderately obese females. DESIGN: Randomized, prospective, long-term cohort study. Subjects performed continuous exercise at 60 ± 75% of maximum aerobic capacity, 3 days per week, 30 min per session, or exercised intermittently using brisk walking for two, 15 min sessions, 5 days per week. MEASURES: Aerobic capacity, body weight, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
110
2
3

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(129 citation statements)
references
References 33 publications
(25 reference statements)
12
110
2
3
Order By: Relevance
“…25 Indeed, the intensity of the test should be carefully tailored to not overwork the cardiocirculatory system, and constant electrocardiographic monitoring as was performed in this study is advised, because structural distortions of the myocardial muscle and heart vessels are not uncommon in this population. [27][28][29] In the present series, no side effects of the modified Bruce test were noticed, and all patients tolerated the exercise very well, despite their substantially altered body composition. Highrisk subjects with arterial hypertension, congestive heart failure, myocardial ischemia, or respiratory insufficiency were obviously eliminated due to the exclusion criteria and thorough preliminary assessment, and subjects were instructed to run only as long as they felt comfortable, avoiding any strenuous efforts.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…25 Indeed, the intensity of the test should be carefully tailored to not overwork the cardiocirculatory system, and constant electrocardiographic monitoring as was performed in this study is advised, because structural distortions of the myocardial muscle and heart vessels are not uncommon in this population. [27][28][29] In the present series, no side effects of the modified Bruce test were noticed, and all patients tolerated the exercise very well, despite their substantially altered body composition. Highrisk subjects with arterial hypertension, congestive heart failure, myocardial ischemia, or respiratory insufficiency were obviously eliminated due to the exclusion criteria and thorough preliminary assessment, and subjects were instructed to run only as long as they felt comfortable, avoiding any strenuous efforts.…”
Section: Discussionmentioning
confidence: 98%
“…17,18 Although few specific references to bariatric candidates could be identified in the literature, it is reasonable to propose that more encouraging outcomes would be elicited if progressive physical conditioning were offered to this population jointly with surgical therapy. [26][27][28][29][30] …”
Section: Discussionmentioning
confidence: 99%
“…Long term studies examining exercise and EI which have monitored EI for between 16 weeks and 18 months in overweight men and women have also demonstrated no significant change in EI across the intervention [29][30][31]. However, the exercise sessions are typically unsupervised and the energy expended low, which may explain the lack of compensation.…”
Section: Exercise and Appetite Responsementioning
confidence: 99%
“…In the end, sixteen randomized controlled trails "RCTs" were identified that fulfilled the criteria described above, three of which were identical and therefore eliminated. Thus the meta-analysis includes a total of thirteen studies [27][28][29][30][31][32][33][34][35][36][37][38][39] (Fig. 1). …”
Section: Methodsmentioning
confidence: 99%